Letter (copy) : re shipment of surgical dressings to Spain - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
041-0087-001 HBM/EKK/140. Ship Owning Dept. Social Insurance. Messrs. J.A. Billmeir & Co., Holland House, Bury Street, LONDON, E.C.3. Dear Sirs, re Shipment of Surgical Dressings to Spain. I have your letter of the 26th inst., and in spite of the very clear understanding that we had on this matter in the early stages, we will agree to your suggestion to split the difference. Therefore I have pleasure in enclosing cheque for £5.4. 0. in settlement of the enclosed account. I shall be glad if you will acknowledge receipt. With thanks for your assistance in this matter. Yours faithfully, Medical Adviser. Cheque. Account. 292/946/41/87